Computational Intelligence Techniques in Diagnosis of Brain Diseases - Gurumoorthy, Sasikumar (SpringerBriefs in Forensic and Medical Bioinformatics,, 2018)
This book highlights a new biomedical signal processing method of extracting a specific underlying signal from possibly noisy multi-channel recordings, and shows that the method is suitable for extracting independent components from the measured electroencephalogram (EEG) signal. The system efficiently extracts memory spindles and is also effective in Alzheimer seizures. Current developments in computer hardware and signal processing have made it possible for EEG signals or "brain waves" to communicate between humans and computers - an area that can be extended for use in this domain.